A Tridimensional Model for NK Cell-Mediated ADCC of Follicular Lymphoma - Decaup, Emilie; Rossi, Cédric; Gravelle, Pauline; Laurent, Camille; Bordenave, Julie; Tosolini, Marie; Tourette, Anne; Perrial, Emeline; Dumontet, Charles; Poupot, Mary; Klein, Christian; Savina, Ariel; et al. (Frontiers in Immunology, 2019)
FFollicular lymphoma (FL) is the second most frequent subtype of B non-Hodgkin’s lymphomas (NHL) for which the treatment is based on the use of anti-CD20 mAbs. NK cells play a crucial role in their mechanism of action and the number of these cells mediating antibody-dependent cell cycotoxicity (ADCC) in the peripheral blood of FL patients predict the outcome. However, their presence in FL biopsies, their activation and their role have been poorly investigated. Moreover, in vitro studies have not deciphered the exact signaling cascades triggered by NK cells in presence of anti-CD20 mAbs on both effector and target cells in a relevant FL model. We performed in silico analyses and ex vivo functional assays to determine the presence and the activation status of NK cells in FL biopsies. We modelized ADCC phenomenon by developing a co-culture model composed by 3D-cultured FL cells and NK cells. Thus, we investigated the biological effect of anti-CD20 mAbs by fluorescent microscopy and the phosphorylation status of survival pathways by cell bar coding phosphoflow in target cells. In parallel, we measured the status of activation of downstream FcγRIIIa signaling pathways in effector cells and their activation (CD69, perforin, granzyme B, IFNγ) by flow cytometry. We determined by in vivo experiments the effects of anti-CD20 mAbs in presence of NK cells in SCID-Beige engrafted FL mice. Here, we show that functional NK cells infiltrate FL biopsies, and that their presence tends to correlate with the survival of FL patients. Using our 3D co-culture model, we show that rituximab and GA101 are able to promote degranulation, CD69 expression, IFNγ production and activate FcγRIIIa signaling cascade in NK cells, and inhibit survival pathways and induce apoptosis in FL cells. The effect of GA101 seems to be more pronounced as observed in vivo in a xenograft FL model. This study strongly supports the role of NK cells in FL and highlights the application of the 3D co-culture model for in vitro validation.